Understanding the Nexus between Traditional and Modern Political Orders in Ghana - E. Aggrey-Darkoh; Bossman E. Asare (Archives of Current Research International, 2015)
There is some consensus among academics, policy analysts, institutionalists, and traditional rulers that the interest of Ghana will be better served if traditional and modern political orders are harmonized. The harmonization has become critical in view of the fact that modern political order has come to stay while traditional political orders have proved very resilient. Using new institutionalism as a theoretical base of the analysis, the paper identified that traditional political orders suffered some turbulence during colonialism largely as a result of the decision of colonial authorities to subsume the traditional political orders under their preferred system of government. The study revealed that attempts at state building, formation of alliances among states and between states and colonial powers to enhance their survival and independence from overbearing neighbors, ensured that colonial authorities had preponderance of influence over traditional orders. Also the decision of post-colonial governments to reward or punish traditional rulers for their roles in colonialism posed a big challenge to the traditional political orders in Ghana. The 1992 Constitution does not enhance the role of traditional orders at all; at best it only places those orders in a subservient position. The paper recommends that in view of the loyalty traditional political orders enjoy and their potential contribution to national development, efforts must be made to craft an enduring relationship between them and modern political orders beyond the symbolic arrangement contained in the 1992 Constitution.